THE 2013 CURRICULUM: STANDS ON TWO CONTRADICTIVE TRADITIONS - Muhidin, Aeng (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2013)
The 2013 Curriculum on history learning is a contradictive combination between the major tradition and alternative tradition. The major tradition focused in morality inculcation, political history material, clarification teaching method, logical thinking, and morality assessment. Challenges in major tradition implementation are (1) value determination, (2) topics election, and (3) learning climate. Alternative tradition appeared as a critic for major tradition. Alternative tradition itself focused in historical skill, history knowledge, and historical method based on learning principle. The main challenges in alternative tradition implementation are mastery in science and learning methods. The major tradition creates attitude competency, included spiritual and social’s value and morality; and alternative tradition creates knowledge and skill competency.